Weibull Model Allowing Nearly Instantaneous Failures. (24th September 2007) - Lai, C. D.; Khoo, Michael B. C.; Muralidharan, K.; Xie, M.
Abstract : A generalized Weibull model that allows instantaneous or early failures is modified so that the model can be expressed as a mixture of the uniform distribution and the Weibull distribution. Properties of the resulting distribution are derived; in particular, the probability density function, survival function, and the hazard rate function are obtained. Some selected plots of these functions are also presented. An R script was written to fit the model parameters. An application of the modified model is illustrated.